Novel polymers: Molecular to nanoscale order in three dimensions - Wooley, Karen L. (The National Academy of Sciences, 2000)
The assembly of polymer chains in solution is a powerful method that is leading to the preparation of interesting and unique macromolecular-based synthetic nanostructures. Specific control over the intramolecular and intermolecular physical interactions dictates either the folding of single chains or the aggregation and ordering of multiple chains. This control is provided through the selective placement of functional groups along the polymer backbone and the relative strengths of their attractive and repulsive interactions.